Inhibitors of the PD-1/PD-L1 axis for the treatment of head and neck cancer: current status and future perspectives - Ran X; Yang K (Dove Medical Press, 2017)
Xiongwen Ran, Kai Yang Department of Oral and Maxillofacial Surgery, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China Abstract: Head and neck cancer (HNC) is a common malignant tumor, but traditional therapeutic methods have unsatisfactory curative effects and many complications occur. Hence, there is an urgent need to develop therapeutic methods that can elicit curative effects as well as low toxic and few side effects. With the development of cancer molecular biology and immunology, targeted therapy for immune checkpoints of programmed cell death 1 (PD-1) and programmed cell death ligand 1 (PD-L1) has shown enormous development prospects for HNC treatment. Groundbreaking progress has been achieved in the treatment of recurrent/metastatic head and neck squamous cell carcinoma (HNSCC). This review describes current treatment by PD-1- and PD-L1-targeted drugs for HNC. Keywords: head and neck cancer, squamous cell carcinoma, programmed cell death 1, programmed cell death ligand 1, immunotherapy, immune checkpoint